Ciboria carunculoides Suppresses Mulberry Immune Responses Through Regulation of Salicylic Acid Signaling - Lv, Zhiyuan; Hao, Lijuan; Ma, Bi; He, Ziwen; Luo, Yiwei; Xin, Youchao; He, Ningjia (Frontiers in Plant Science, 2021)
Ciboria carunculoides is the dominant causal agent of mulberry sclerotial disease, and it is a necrotrophic fungal pathogen with a narrow host range that causes devastating diseases in mulberry fruit. However, little is known about the interaction between C. carunculoides and mulberry. Here, our transcriptome sequencing results showed that the transcription of genes in the secondary metabolism and defense-related hormone pathways were significantly altered in infected mulberry fruit. Due to the antimicrobial properties of proanthocyanidins (PAs), the activation of PA biosynthetic pathways contributes to defense against pathogens. Salicylic acid (SA) and jasmonic acid (JA) are major plant defense hormones. However, SA signaling and JA signaling are antagonistic to each other. Our results showed that SA signaling was activated, while JA signaling was inhibited, in mulberry fruit infected with C. carunculoides. Yet SA mediated responses are double-edged sword against necrotrophic pathogens, as SA not only activates systemic acquired resistance (SAR) but also suppresses JA signaling. We also show here that the small secreted protein CcSSP1 of C. carunculoides activates SA signaling by targeting pathogenesis-related protein 1 (PR1). These findings reveal that the infection strategy of C. carunculoides functions by regulating SA signaling to inhibit host defense responses.